Pollution and Law - Nicolau, Ingrid Ileana (Technium Social Sciences Journal, 2021)
Pollution comes from latin word polluero-ere, and means dirty, profane. It designates an action through which the man degrades -”dirty” - its own environment. Modern dictionaries contain both short definition for pollution, limited to its effects over environment as well as a general view of the pollution which contains a large group of negative influences. Pollution can be chemical, physical, biological, genetic, esthetic etc. Due to many environment tragedies during the first half of the XX century, many nations imposed extensive laws that are designed to repair the damages caused by previously uncontrolled pollution and to prevent further environments contaminations. Pollution, through the nature of social-economic and humanitarian consequences that produces and of their influence area is an issue with national and international implications